1982
DOI: 10.1111/j.1476-5381.1982.tb08757.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF HISTAMINE ON THE RESTING AND STIMULATION‐INDUCED RELEASE OF [3H]‐NORADRENALINE IN GUINEA‐PIG ISOLATED ATRIA

Abstract: The sympathetic transmitter stores of guinea‐pig isolated atria were labelled with [3H]‐noradrenaline. The effects of histamine (0.3 to 100 μmol/l) on resting and stimulation‐induced (S‐I, 2 Hz for 10 s) release of radioactivity were investigated. Histamine, in low concentrations (0.3 and 1 μmol/l) had no effect on resting release but inhibited S‐I release of radioactivity. The inhibition was abolished by the H2‐receptor antagonist, cimetidine (10 μmol/l) and also by the H1‐receptor antagonist, mepyramine (1μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

1982
1982
1996
1996

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
0
6
2
Order By: Relevance
“…Our finding that histamine attenuated cardiac responses to adrenergic stimulation without reducing NEO was at variance with the view held by others (Rand et al, 1982;McGrath and Shepherd, 1976;Kimura and Satoh, 1983;Lockhandwala, 1978) that histamine inhibits NE release from sympathetic nerve endings. We reasoned that, since NEO represents a small fraction of the NE actually released from sympathetic nerves, the uptake of released NE by various sites might have contributed to our inability to detect a significant reduction of NEO by histamine.…”
Section: Amplification Of Norepinephrine Overflow By Drugs and Effeccontrasting
confidence: 59%
See 2 more Smart Citations
“…Our finding that histamine attenuated cardiac responses to adrenergic stimulation without reducing NEO was at variance with the view held by others (Rand et al, 1982;McGrath and Shepherd, 1976;Kimura and Satoh, 1983;Lockhandwala, 1978) that histamine inhibits NE release from sympathetic nerve endings. We reasoned that, since NEO represents a small fraction of the NE actually released from sympathetic nerves, the uptake of released NE by various sites might have contributed to our inability to detect a significant reduction of NEO by histamine.…”
Section: Amplification Of Norepinephrine Overflow By Drugs and Effeccontrasting
confidence: 59%
“…(Circ Res 54: 516-526, 1984) IN ADDITION to its direct actions on the heart (see review by Levi et al, 1982), histamine has been reported to modulate adrenergic responses in cardiovascular tissues. In support of this notion are the observations that histamine reduces the field stimulation-induced efflux of radioactivity from [ 3 H]norepinephrine-preloaded guinea pig atrial tissue (Rand et al, 1982), and dog saphenous vein and tibial artery (McGrath and Shepherd, 1976). It has also been shown that histamine depresses the positive chronotropic response to right cardiac sympathetic nerve stimulation in the dog, whereas it does not reduce the chronotropic response to intravenously administered norepinephrine (NE) (Lockhandwala, 1978;Kimura and Satoh, 1983).…”
Section: Release Of Histamine By Sympathetic Nerve Stimulation In Thementioning
confidence: 90%
See 1 more Smart Citation
“…The effects of PEA (30 pmol/l) were unaltered by the presence of mepyramine (0.1 plmol/l) or metoprolol (0.1 lumol/l) (Table 2). The ability of histamine to inhibit responses to noradrenergic nerve stimulation by activating prejunctional receptors has previously been reported for canine saphenous vein and tibial artery strips (McGrath & Shepherd, 1976), the canine heart in situ (Lokhandwala, 1978), the canine isolated blood-perfused gracilis muscle (Powell, 1979) and guinea-pig isolated atria (Wong-Dusting et al, 1979;Rand et al, 1982). The histamine receptors involved appeared to be of the H2-type.…”
Section: Effect Of 2-(2-pyridyl)-ethylaminementioning
confidence: 74%
“…Further, the suppressive effect of HA on cold-stimulated TSH secretion would rather be a consequence ofneurosympathetic blockade than of increased sympathetic activity. Although HA is known to inhibit sympathetic transmission in dogs and guinea pigs when given peripherally [31,32], it is most obvious that HA (1 and 2.5 /lg/rat), given i.c.v., does not inhibit the peripheral sympathetic nervous system.…”
Section: Treatmentmentioning
confidence: 99%